Carbonate slope re‐sedimentation in a tectonically‐active setting (Western Sicily Cretaceous Escarpment, Italy). Issue 5 (5th March 2020) - Randazzo, Vincenzo; Le Goff, Johan; Di Stefano, Pietro; Reijmer, John; Todaro, Simona; Cacciatore, Maria Simona
Abstract: Tectonic processes are widely considered as a mechanism causing carbonate platform margin instabilities leading to the emplacement of mass transport deposits and calciturbidites. However, only few examples establishing a clear link between tectonics and re‐sedimentation processes are known from the literature. The two‐dimensional and three‐dimensional wire‐cut walls of hundreds of quarries extracting ornamental limestones (for example, Perlato di Sicilia ) from the Western Sicily Cretaceous Escarpment in Italy expose a series of mass transport deposits. The depositional architecture, spatial facies distribution and sedimentary features of these deposits were studied in detail. Thin section analysis was used to define the microfacies characteristics and to determine the age of the re‐sedimented limestones. Eleven facies types grouped into four facies associations were recognized that defined specific depositional processes and environments. The stratigraphic architecture of the slope was reconstructed using four composite facies successions based on the detailed analysis and correlation of the field sections. The palaeoslope orientation was reconstructed based on the analysis of synsedimentary faults, slump scars and pinch‐out geometries. The Western Sicily Cretaceous Escarpment was strongly influenced by synsedimentary transtensional tectonics in combination with magmatic processes, as suggested by the presence of tuffites and pillow lava intercalations within the re‐sedimented carbonate series. These volcanics point to a major role of crustal shear as a trigger for mass transport deposit emplacement. The facies distribution along the Western Sicily Cretaceous Escarpment delivers new insights into the deformation processes accompanying the crustal extension of the Cretaceous western Tethys realm.